Chatting with Al Capone: Leveraging virtual conversational agents in emotional landscapes - Nisha Sriganesh; Allyson Eamer (Australian Journal of Applied Linguistics)
This article explores the extent to which virtual conversational agents generated by artificial intelligence (AI) are being leveraged by language learning apps to develop social, emotional and intercultural skills in language learners.  While the affordances of natural language processing (NLP) technology are well-documented in the cognitive domains of language learning (e.g. vocabulary acquisition, grammar), significantly less research has explored how learners’ interactions with virtual conversational agents can build socio-emotional and intercultural competence. We engage in dialogues within three popular apps (Duolingo, ImmerseMe and MakesYouFluent) to determine how these apps are equipping language learners to navigate emotional landscapes. We conclude that app developers and instruction designers are under-valuing the role of social, emotional, and intercultural learning in second language acquisition and/or are underusing the potential of AI and NLP to develop competence in these areas